Crystal structure and Hirshfeld surface analysis of the layered hybrid metal halide poly[bis(2-iodoethylammonium) [di-μ-iodido-diiodidogermanate(II)]] - Olesia I. Kucheriv; Mircea-Odin Apostu; Olena Prysiazhna; Vadim A. Potaskalov; Sergey O. Malinkin (Acta Crystallographica Section E: Crystallographic Communications)
The title compound is a germanium-based hybrid metal halide that represents a less-toxic alternative to more popular lead-based analogues in optoelectronic applications. {(2-IC2H4NH3)2[GeI4]}n is composed of infinite inorganic layers that are formed by [GeI6]4− octahedra connected in a corner-sharing manner with four equatorial I atoms. The organic (2-IC2H4NH3)+ cations interleave the inorganic layers. There are two types of 2-iodoethylammonium cations, with synclinal and antiperiplanar conformations. The organic cations interact with the inorganic layers through hydrogen bonds and I...I contacts. The crystal under investigation was twinned by a 180° rotation around [100].